(untitled) (Current Horticulture, 2024)
The Orchidaceae is one of the largest families of flowering plants comprising about 40 per cent of the Monocotyledons. India, due to its tropical location, physiological variation associated with favourable climatic conditions, has a moderately rich orchid flora of about 1350 species in 186 genera. The structure of leaf and leaf basis are taken primary importance in this paper. On this investigation, the anatomy of leaf of Bulbophyllum species is taken for the detailed study, to find out the ecological and taxonomic significance.